The iron‐stress activated RNA 1 (IsaR1) coordinates osmotic acclimation and iron starvation responses in the cyanobacterium Synechocystis sp. PCC 6803. (26th March 2018) - Rübsam, Henriette; Kirsch, Friedrich; Reimann, Viktoria; Erban, Alexander; Kopka, Joachim; Hagemann, Martin; Hess, Wolfgang R.; Klähn, Stephan
Summary: In nature, microorganisms are exposed to multiple stress factors in parallel. Here, we investigated the response of the model cyanobacterium Synechocystis sp. PCC 6803 to simultaneous iron limitation and osmotic stresses. Iron is a major limiting factor for bacterial and phytoplankton growth in most environments. Thus, bacterial iron homeostasis is tightly regulated. In Synechocystis, it is mediated mainly by the transcriptional regulator FurA and thei ron‐s tressa ctivatedR NA1 (IsaR1). IsaR1 is an important riboregulator that affects the acclimation of the photosynthetic apparatus to iron starvation in multiple ways. Upon increases in salinity, Synechocystis responds by accumulating the compatible solute glucosylglycerol (GG). We show that IsaR1 overexpression causes a reduction in the de novo GG synthesis rate upon salt shock. We verified the direct interaction between IsaR1 and the 5′UTR of the ggpS mRNA, which in turn drastically reduced the de novo synthesis of the key enzyme for GG synthesis, g lucosylg lycerolp hosphates ynthase (GgpS). Thus, IsaR1 specifically interferes with the salt acclimation process in Synechocystis, in addition to its primary regulatory function. Moreover, the salt‐stimulated GgpS production became reduced under parallel iron limitation in WT – an effect which is, however, attenuated in an isaR1 deletion strain. Hence, IsaR1 is involved in the integration of the responses to different environmental perturbations and slows the osmotic adaptation process in cells suffering from parallel iron starvation.